Staphylococcus aureus in Atopic Dermatitis: Past, Present, and Future. Issue 4 (July 2020) - Hwang, Jonwei; Jaros, Joanna; Shi, Vivian Y.
Abstract : N/A: The role of Staphylococcus aureus (SA) in the pathogenesis and management in atopic dermatitis is rapidly evolving. The modern understanding of SA in atopic dermatitis now includes an expanded array of virulence factors, the interplay of clonal and temporal shifts in SA populations, and host factors such as filaggrin and natural moisturizing factor. New, emerging therapies that focus on long-term, targeted elimination of SA colonization are currently under investigation ( Br J Dermatol 2017;17(1)63–71). Herein, we discuss and review the latest staphylococcal and microbiome-modifying therapies including topical antibiotics, topical natural oil fatty acids, anti-SA vaccines, microbial transplantation, vitamin D supplementation, dupilumab and proposed future investigative directions.